A Brief History of Mechanical Engineering - Dixit, Uday Shanker; Hazarika, Manjuri; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
What is mechanical engineering? What a mechanical engineering does? How did the mechanical engineering change through ages? What is the future of mechanical engineering? This book answers these questions in a lucid manner. It also provides a brief chronological history of landmark events and answers questions such as: When was steam engine invented? Where was first CNC machine developed? When did the era of additive manufacturing start? When did the marriage of mechanical and electronics give birth to discipline of mechatronics? This book informs and create interest on mechanical engineering in the general public and particular in students. It also helps to sensitize the engineering fraternity about the historical aspects of engineering. At the same time, it provides a common sense knowledge of mechanical engineering in a handy manner.
What is Mechanical Engineering -- Landmark Revolutionary Inventions in Mechanical Engineering -- History of Mechanics -- History of Thermodynamics -- Manufacturing -- Emergence of Production and Industrial Engineering -- History of Mechatronics -- Future of Mechanical Engineering.
Keywords: Mechanical engineering; Science -- History; Engineering; Technology -- Sociological aspects; Mechanical Engineering; History of Science; Technology and Engineering; Science, Technology and Society